Efficacy, Cost-Effectiveness, And Risk-Benefit Analysis Of Three Herbicides In Immature Oil Palm Plantation - Wibawa, Wahyu (2007)

(untitled)
Field experiment and survey were conducted at Malaysian Airport Berhad (MAB) Agriculture-Horticulture Sdn. Bhd., Sepang, Selangor. Laboratory and glass-house experiments were done at the Faculty of Agriculture, Universiti Putra Malaysia, Serdang. Two-year old oil palm planted in the plantation was used in the experiment. Paraquat, glufosinate-ammonium and glyphosate were used as treatments. The experimental design was a randomized complete block design (RCBD) with four replications. The general objective of this study was to evaluate the performance and impact of three commonly used broad-spectrum herbicides, namely, paraquat, glufosinate-ammonium and glyphosate on cost, production, environment and safety. Efficacy, short term weed dynamic, oil palm growth, fungi and bacteria population in soil, residual phytotoxicity effect, residue analysis, and risk-benefit analysis of the three broad-spectrum herbicides were determined and evaluated in the experiment. Paraquat at 200 and 400 g a.i. ha-1 were not effective to control weeds, whereas at 600 and 800 g a.i. ha-1 were effective with the duration of effective weed control of 8.75 and 11.75 weeks, respectively. Glufosinate-ammonium at 200 g a.i. ha-1 and glyphosate at 400 g a.i. ha-1 gave excellent weed control, within the duration of effective weed control of 15 and 14.5 weeks, respectively. Thus, efficacy of glufosinate-ammonium and glyphosate was better than paraquat. Treatments with glufosinate-ammonium and glyphosate increased densities of broadleaf weed, but not on grass and total weed densities. Paraquat treatments did not cause weed shifting, whereas both glufosinate-ammonium and glyposate treatments caused shifting in the weed species composition. A round of paraquat sprayed at 200, 400, 600, and 800 g a.i. ha-1, glufosinate-ammonium at 200, 400, 600, and 800 g a.i. ha-1, and glyphosate at 400, 800, 1200, and 1600 g a.i. ha-1 did not increase herbicide residues in the soil. Using paraquat, glufosinate-ammonium, and glyphosate for controlling weeds were safe for vegetative (plant height, the number of fronds/plant) and generative (number of fruit bunches/plant) growths of oil palm. Severe weed competition affected number of fruit bunch of oil palm significantly, especially at early maturation stages. Using paraquat, glufosinate-ammonium, and glyphosate for controlling weeds in immature oil palm did not affect bacteria and fungi populations in the soil. The herbicides applied at range of recommended dose were safe not only to oil palm crops but also for bacteria and fungi as expressed by their populations. Paraquat, glufosinate-ammonium, and glyphosate residues in soil did not cause adverse effects (risk) on seed germination and growth components (plant height, leaf area, root length, and total dry weight) of corn and cucumber seedlings in bioassay study conducted. At the range of recommended application doses, paraquat, glufosinate-ammonium, and glyphosate were safe for seed germination and plant growth. Paraquat has unacceptable risk to human health, especially to the applicators. Paraquat at 800 g a.i./ha is quite costly (RM 310.80/ha/year) to get the satisfactory weed control. The risk of paraquat clearly outweighed its benefit. Glufosinate-ammonium has acceptable risk level to human health and environment. Glufosinate-ammonium require medium cost (RM 214.19/ha/year) to get to the satisfactory weed control. Glufosinate-ammonium can be used as alternate herbicide to avoid weed resistance. Glyphosate has acceptable risk to human health and environment, and lower cost (RM 108.95/ha/year) to get to the satisfactory level of weed control. The benefit of glyphosate clearly outweighed its risk. This herbicide should be recommended widely because of its efficacy, cost-effectiveness, and safety. However, alternate herbicide is needed to avoid broadleaf weeds resistance. Safe and effective use of herbicides in oil palm plantations were depend significantly on herbicide knowledge, experience, and formal education of the applicators. Handling and using herbicides safely were available, but preventive measures are costly. The use of dangerous herbicides should be restricted, when preventive behavior can not be used as a method of controlling the health risks associated with herbicides.